2020
DOI: 10.1042/cs20201036
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of interleukin-6 signaling attenuates aortitis, left ventricular hypertrophy and arthritis in interleukin-1 receptor antagonist deficient mice

Abstract: The aim of this study was to examine whether inhibition of Interleukin (IL)-6 signaling by MR16-1, an IL-6 receptor antibody, attenuates aortitis, cardiac hypertrophy, and arthritis in IL-1 receptor antagonist deficient (IL-1RA KO) mice.  Four weeks old mice were intraperitoneally administered with either MR16-1 or non-immune IgG at dosages that were adjusted over time for 5 weeks.  These mice were stratified into 4 groups: MR16-1 treatment groups, KO/MR low group (first 2.0 mg, following 0.5 mg/week, n=14) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 69 publications
2
5
0
Order By: Relevance
“…However, we found a significantly higher number of IL-1β- and IL-6-positive cells in the IL1rn −/− group within the abdominal aortic wall. This study, therefore, corroborates the preferential involvement of these two cytokines in the pathophysiology of this model, as previously observed in this mouse model and in GCA based on fundamental and targeted cytokine therapeutic data [ 15 , 28 32 ]. Second, considering second-generation mice, the TBR measured on PET-MR was significantly higher in the descending thoracic aorta of five 9-week-old IL1rn −/− mice born and housed in an SPF environment than in the wild-type group, suggesting a role of the microbiota, probably that in the gut [ 33 ], in the induction of inflammatory aortitis in this model.…”
Section: Discussionsupporting
confidence: 90%
“…However, we found a significantly higher number of IL-1β- and IL-6-positive cells in the IL1rn −/− group within the abdominal aortic wall. This study, therefore, corroborates the preferential involvement of these two cytokines in the pathophysiology of this model, as previously observed in this mouse model and in GCA based on fundamental and targeted cytokine therapeutic data [ 15 , 28 32 ]. Second, considering second-generation mice, the TBR measured on PET-MR was significantly higher in the descending thoracic aorta of five 9-week-old IL1rn −/− mice born and housed in an SPF environment than in the wild-type group, suggesting a role of the microbiota, probably that in the gut [ 33 ], in the induction of inflammatory aortitis in this model.…”
Section: Discussionsupporting
confidence: 90%
“…In the transcriptome sequencing experiment, we found that IL-13Rα2, Tnfaip3, Tnfrsf14, and Tnfrsf9 were upregulated in TNF-α-stimulated RAW264.7 cells, which was related with the development of inflammation (Wilson et al, 2011). The expression of Il1rn was upregulated in WBT + TNFα-stimulated RAW264.7 cells, suggesting WBT could ameliorate inflammatory conditions stimulated by TNF-α (Matsuki et al, 2005;Hada et al, 2020). These findings were consistent with ELISA results about IL-1β and IL-6.…”
Section: Discussionsupporting
confidence: 83%
“…Left ventricular diastolic dysfunction, in fact, has been associated to the release of pro-inflammatory cytokines, prolonged hypoxemia, and excessive activation of neuroendocrine and autonomic nerve function, further aggravating the hormonal storms that foster myocardial hypertrophy and fibrosis ( 32 ). Experimental evidence has shown that blockade of interleukin 6, a typical inflammatory cytokine, attenuates left ventricular hypertrophy ( 33 ).…”
Section: Discussionmentioning
confidence: 99%